Development and characterization of cefoxitin loaded D,L-PLA nanoparticles - Machado, Silvia Regina Pengo; Evangelista, Raul Cesar [UNESP] (My University, 2010)
Nanoparticles containing cefoxitin (CEF) made of D,L-PLA (PLA) were designed by a multiple emulsion/solvent evaporation method. The particles were extensively evaluated in relation to morphology, encapsulation efficiency, drug-polymer interactions as well as in vitro drug release kinetics. Nanoparticles were spherical in shape and isolated, with a mean diameter of about 600 nm. The thermal behaviour (DSC) of CEF-containing nanoparticles suggested that the drug was dispersed at a molecular level within the system. The drug encapsulation efficiency in the system for a CEF concentration of 30 mg/mL was 5.5%, as assessed after the drug extraction, by a validated HPLC method. This low encapsulation efficiency is understandable, since CEF is highly hydrophilic. The in vitro assays showed a strong sustained drug release profile from the nanoparticles with kinetics following pure Fickian diffusion.

As nanopartículas de D, L-PLA (PLA) contendo cefoxitina (CEF) foram preparadas pelo método de emulsão múltipla / evaporação do solvente. As partículas foram avaliadas em relação à morfologia, à eficiência de encapsulação, às interações polímero-fármaco, bem como à cinética de liberação do fármaco in vitro . As nanopartículas são esféricas e isoladas, com um diâmetro médio de cerca de 600 nm. O comportamento térmico (DSC) das nanopartículas contendo CEF sugeriu que o fármaco está disperso em um nível molecular dentro do sistema. A eficiência de encapsulação do fármaco no sistema quando a concentração de CEF é 30 mg / mL foi de 5,5%, determinada após a extração de fármaco, através de um método de HPLC validado. Esta baixa eficiência de encapsulação é compreensível, uma vez que a CEF é altamente hidrofílica. Os ensaios in vitro mostraram um perfil de liberação do fármaco a partir das nanopartículas fortemente sustentado e com uma cinética de difusão Fickiana pura.
Desenvolvimento e caracterização de nanopartículas de D,L-PLA contendo cefoxitina
Keywords: Nanoparticles; Controlled release; D,L-PLA; Cefoxitin; In vitro release; Nanopartículas; Liberação controlada; D,L-PLA; Cefoxitina; Liberação In vitro